2017
DOI: 10.1590/0004-282x20170030
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit/hyperactivity disorder: the impact of methylphenidate on working memory, inhibition capacity and mental flexibility

Abstract: Objective To compare children with attention-deficit/hyperactivity disorder (ADHD), before and after the use of methylphenidate, and a control group, using tests of working memory, inhibition capacity and mental flexibility. Methods Neuropsychological tests were administrated to 53 boys, 9–12 years old: the WISC-III digit span backward, and arithmetic; Stroop Color; and Trail Making Tests. The case group included 23 boys with ADHD, who were combined type, treatment-naive, and with normal intelligence withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
5
0
3
Order By: Relevance
“…It should be noted that working memory underlies the central executive component of executive functioning (Engle, Laughlin, Tuholski, & Conway, 1999) and is the one executive function task that is most consistently impaired in children with ADHD (Kofler et al, 2019). However, previous studies did report positive effects of methylphenidate on response inhibition, attentional flexibility and psychomotor speed in treatment-na€ ıve children with ADHD (Bolfer et al, 2017;Coghill, Seth, et al, 2014;Konrad, Neufang, Fink, & Herpertz-Dahlmann, 2007;Pietrzak et al, 2006). Our null findings could result from a diminishing effect after long-term use due to developing tolerance for methylphenidate (Wang et al, 2013), although an assessment prior to starting methylphenidate treatment would be necessary to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that working memory underlies the central executive component of executive functioning (Engle, Laughlin, Tuholski, & Conway, 1999) and is the one executive function task that is most consistently impaired in children with ADHD (Kofler et al, 2019). However, previous studies did report positive effects of methylphenidate on response inhibition, attentional flexibility and psychomotor speed in treatment-na€ ıve children with ADHD (Bolfer et al, 2017;Coghill, Seth, et al, 2014;Konrad, Neufang, Fink, & Herpertz-Dahlmann, 2007;Pietrzak et al, 2006). Our null findings could result from a diminishing effect after long-term use due to developing tolerance for methylphenidate (Wang et al, 2013), although an assessment prior to starting methylphenidate treatment would be necessary to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for working memory and planning, 3 previous studies have reported significant, positive effects but were all uncontrolled ( Fallu et al, 2006 ; Ginsberg et al, 2012 ; Ni et al, 2013 ). Controlled children’s studies have found mixed effects of methylphenidate treatment for these functions (e.g., Coghill et al, 2007 ; Cristiana et al, 2017 ; Kortekaas-Rijlaarsdam et al, 2017 ; Morell and Expósito, 2017 ). Two randomized control trial (RCT) studies indicate positive, significant effects of methylphenidate for measures of response inhibition ( Bouffard et al, 2003 ; Boonstra et al, 2005 ), but these and 2 additional studies ( Ni et al, 2013 ; Bron et al, 2014 ) also report nonsignificant findings.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the results of previous studies which found that the prevalence of ADHD was greater in boys (6,20,21) . Psychostimulant methylphenidate (MPH) and amphetamine (AMPH) are the first-line ADHD drug choice (22)(23)(24)(25) Both of these drugs primarily work on dopamine (D2) and noradrenaline (NA) system, but not on the serotonin system (8,26) . More than half of the subjects did not respond positively to the administration of this psychostimulant (6,27) Not all parents agree with methylphenidate that affects appetite and inhibits growth when given to their children and also the risk of drug dependence or abuse on long-term use with adolescent subject (28) .…”
Section: Discussionmentioning
confidence: 99%